Theories of state recognition - Nicholson, Rowan; Grant, Thomas D. (Routledge Handbook of State Recognition, 2020)
This chapter provides an overview of the main competing theories. The first two theories discussed are the traditionally dominant debates of 'declaratorism' and 'constitutivism'. That discussion is followed by a survey of approaches that take elements from both traditional theories and concludes with observations on collective non-recognition. The debate is not merely a matter of nuance; the theories disagree radically about the legal significance of recognition. One reason for the profusion of theories and literature is that recognition is intertwined with basic or philosophical questions about international law: what states are and how they come into being, whether international law is an 'objective' system, and whose will or values it is designed to serve. So long as those larger questions continue to excite interest and divide opinion, international lawyers are likely to continue to disagree about the legal significance of recognition.